2008
DOI: 10.1111/j.1365-313x.2008.03435.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel cis‐regulatory element for UV‐B‐induced transcription in Arabidopsis

Abstract: SummaryUltraviolet-B light (UV-B) regulates the expression of genes in a wavelength-and fluence rate-dependent fashion. A signaling pathway consisting of CONSTITUTIVE PHOTOMORPHOGENESIS 1 (COP1) and UV RESISTANCE LOCUS 8 (UVR 8) mediates responsiveness to longer wavelength, low intensity UV-B lightactivating, for example, HY5 gene expression. By contrast, transcription of another group of genes, including ANAC13, modulated by shorter wavelength, higher intensity UV-B is controlled by a yet unknown and largely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 39 publications
(118 reference statements)
3
51
0
Order By: Relevance
“…Consistent with microarray analysis (Kilian et al, 2007) and reporter assays done by other laboratories (Safrany et al, 2008), our experiments showed that a pulse UV-B under continuous white light caused a strong increase (77.2-fold: from 8.0 3 10 2 at 0 h to 6.2 3 10 4 cpm seedling -1 at 3 h) in luciferase activity in plants carrying luciferase under the control of the native ELIP2 promoter. This peak of activity occurred 3 h after the UV-B pulse (Fig.…”
Section: Uv-b Responsesupporting
confidence: 90%
“…Consistent with microarray analysis (Kilian et al, 2007) and reporter assays done by other laboratories (Safrany et al, 2008), our experiments showed that a pulse UV-B under continuous white light caused a strong increase (77.2-fold: from 8.0 3 10 2 at 0 h to 6.2 3 10 4 cpm seedling -1 at 3 h) in luciferase activity in plants carrying luciferase under the control of the native ELIP2 promoter. This peak of activity occurred 3 h after the UV-B pulse (Fig.…”
Section: Uv-b Responsesupporting
confidence: 90%
“…We previously analyzed specific responses to UV-B at the level of transcriptomic change (6,11) and confirmed the transcriptional activation of several genes using the luciferase reporter (including At5g52250; see below) (16). We selected two genes induced early in response to narrowband UV-B irradiance encoding highly similar WD40-repeat proteins for detailed analysis.…”
Section: Resultsmentioning
confidence: 95%
“…The ANAC013 promoter also contained the MDM cis-regulatory element (CTTGGAGAAGAAG; see Supplemental Table 3 online) that overlapped with two ANAC013 promoter elements shown previously to be required for UV-B induction of ANAC013 (Safrany et al, 2008). To examine the effect of ANAC013 on its own promoter activity, ProANAC013 fused to b-glucuronidase (GUS) constructs (ProANAC013:GUS) were transformed in 35S:ANAC013-6 plants.…”
Section: Anac013 Autoregulates Its Promoter Activitymentioning
confidence: 99%